Peranan Pendidikan Islam dalam Mengatasi Pergaulan Bebas - Astuti, Mardiah; ismail, Fajri; Herlina, Herlina; Kusnia, Ulfa; Nisa, Fatika Madinatun (Universitas Batanghari Jambi, 2024)
This study aims to describe the explanation of promiscuity, factors of promiscuity, forms of promiscuity in the current generation, the negative impact of promiscuity, and Islamic education efforts in responding to promiscuity. The method used is qualitative descriptive and library research approach. Based on the results of the study shows that the rise of promiscuity that occurs in the current generation and the role of Islamic education in overcoming promiscuity. The results of this study show that promiscuity among today's generation adolescents is caused by the family environment, technological advances and the surrounding environment from these various factors have an impact on decreasing student achievement, dropping out of school and pregnancy out of wedlock.